Efficient Operator Marching Method for Analyzing Crossed Arrays of Cylinders (Communications in Computational Physics, 2020)
Periodic structures involving crossed arrays of cylinders appear as specialthree-dimensional photonic crystals and cross-stacked gratings. Such a structure consistsof a number of layers where each layer is periodic in one spatial direction andinvariant in another direction. They are relatively simple to fabricate and have foundvaluable applications. For analyzing scattering properties of such structures, generalcomputational electromagnetics methods can certainly be used, but special methodsthat take advantage of the geometric features are often much more efficient. In thispaper, an efficient method based on operators mapping electromagnetic field componentsbetween two spatial directions is developed to analyze structures with crossedarrays of circular cylinders. The method is much simpler than an earlier method basedon similar ideas, and it does not require evaluating slowly converging lattice sums.